Fracturing of organic-rich shale during heating - Yurikov, A.; Pervukhina, M.; Lebedev, Maxim; Shulakova, V.; Uvarova, Y.; Gurevich, Boris (SEG, 2013)
Organic-rich shales, traditionally considered as source rocks, have recently become an ambitious goal for oil and gas industry as important unconventional reservoirs. Understanding of initiation and development of fractures in organic-rich shales is crucially important as they drastically increase permeability of these low permeable shales. Fracturing can be induced by rapid decomposition of organic matter caused by either natural heating, such as emplacement of magmatic bodies into sedimentary basins or thermal methods used for enhanced oil recovery. In this study we integrate laboratory experiment and numerical modeling to study fracture development in organic-rich shale. At the first step, we heat a cylindrical sample up to the temperature of 330 degrees Celsius. At the second step, we obtain high resolution microtomographic images of the sample. Large kerogen-filled pores and cracks initiated by the heating can be identified from these images. We repeat these steps for several temperatures in the range 330-430 degrees. The microtomographic images are processed using AVIZO (Visualization Sciences Group) to estimate the dependency between the total area of fractures and the temperature experienced by the sample. Total organic carbon content is tested in the samples experienced the same temperatures. This approach enables a quantitative analysis of fracture initiation and development in organic-rich shales during heating.